Reading between the lines: molecular characterization of five widely used canine lymphoid tumour cell lines. (23rd November 2011) - Seiser, E. L.; Thomas, R.; Richards, K. L.; Kathryn Kelley, M.; Moore, P.; Suter, S. E.; Breen, M.
Abstract : Molecular characterization of tumour cell lines is increasingly regarded as a prerequisite for defining their validity as models of in vivo neoplasia. We present the first comprehensive catalogue of genomic and transcriptional characteristics of five widely used canine lymphoid tumour cell lines. High‐resolution microarray‐based comparative genomic hybridization defined their unique profiles of genomic DNA copy number imbalance. Multicolour fluorescence in situ hybridization identified aberrant gains of MYC, KIT and FLT3 and deletions of PTEN and CDKN2 in individual cell lines, and also revealed examples of extensive structural chromosome reorganization. Gene expression profiling and RT‐PCR analyses defined the relationship between genomic imbalance and transcriptional dysregulation in each cell line, clarifying their relevance as models of discrete functional pathways with biological and therapeutic significance. In combination, these data provide an extensive resource of molecular data for directing the appropriate use of these cell lines as tools for studying canine lymphoid neoplasia.